STRUCTURE AND FORMATION OF ABILITIES - Faizyeva Gulzoda Ulugbekova (American Journals Publishing, 2023)
The driving force of humanity is creative individuals. Identifying such personalities is an urgent task of psychology. Therefore, the study of the structure of abilities and talent is very important both for the theory of psychology, and for solving the specific psychological and educational problems of modern education.
Keywords: Mental talent, displays of talent, structure and formation of abilities, high level of creativity.